The relationship between managers' disclosure tone and the trading volume of investors - Azam Pouryousof; Farzaneh Nassirzadeh; Reza Hesarzadeh; Davood Askarany (Journal of Risk and Financial Management, 2022)
The present research investigates the relationship between managers' disclosure tone and the trading volume of small and large investors separately. The inconsistency of disclosure tone and abnormal trading volume generally indicates information asymmetry between managers and investors. However, by separating the abnormal trading volume of minor investors from major investors, this relationship shows the information asymmetry between minor and major investors. In this research, the disclosure tone of management discussion and analysis (MD&A) is measured using Loughran and McDonald's (L&M) finance-oriented dictionaries, and tone inconsistency is measured using a benchmark model. The data were collected from 143 companies listed on the Tehran Stock Exchange from 2011 to 2020, totalling 1380 annual reports. The results show that MD&A tone inconsistency positively correlates with abnormal trading volume for all investors. In addition, MD&A tone inconsistency has a different impact on the trading behaviour of small and large investors and misleads the former. The present research contributes to the literature by providing evidence of the relationship between MD&A tone inconsistency and abnormal trading volume of small and major investors. It also uses both common words and word combinations to measure tone.
Keywords: 650; trading volume; net purchase of shares; small investors; tone inconsistency; writing tone